The decline of music magazines in Greece - Papathanassopoulos, Stylianos (2024)
Greek music magazines have witnessed a sharp decline over the years. This study posits that this decline cannot be attributed solely to the advent of the internet but is the culmination of various factors. The challenges faced by Greek music magazines resonate with those faced by the broader Greek newspaper industry, suggesting an interlinked adversity within the media landscape. A primary concern has been the saturation of the market; Greece had an unsustainable number of titles for its relatively small market. The country's financial crisis, in tandem with the rise of the internet, led to a significant drop in advertising revenues that traditionally supported these publications. Our findings indicate that from 1946 to 2022, there were 73 distinct music magazine and fanzine titles in Greece. Yet, as of now, only four remain in circulation. This paper delves into the historical significance of music magazines, elucidating their pivotal role in disseminating music culture in Greece, with particular attention directed towards elucidating the factors contributing to their contemporary decline.